Volume change behavior of unsaturated soils due to suction - Tang, Hui Gang; Kohgo, Y.; Shibuya, S.; Bergado, Dennes T.; Asian Institute of Technology (Bangkok : Asian Institute of Technology, 1997)
Collapse and expansive phenomena are typical behaviors of unsaturated soils. Suction significantly influences on volume change behavior of unsaturated soils. A number of natural disaster in the world is occurs resulting from the mechanical behavior of unsaturated soil, like Northeast of Thailand. In order to investigation the volume change behavior of unsaturated soils due to suction, two experimental tests, which are conventional oedometer test and pressure plate test, were adopted in this study. The generalized elastoplastic model proposed by Kohgo et al. (1993) was used to analysis and predict the volume change behavior of unsaturated soils based on experimental test results. Forty-eight of oedometer tests were carried out at various degrees of saturation, and 5 pressure plate tests were performed at slurry sample (nearly 100 percent saturation). Both tests are conducted on Yellow soil and Mixed soil. Yellow soil is collected around Khon Kaen city. Mixed soil consists of 80 % of Yellow soil and 20% Bangkok clay. The results obtained from conventional consolidation tests and suction consolidation tests show that the predicted and measured void ratio agree well in the plastic range of deformation. Yellow soil is typical collapsible soil. The volume change behavior of unsaturated soils can be predicted by Kohgo et al.' s elastoplastic model.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Civil Engineering
Thesis (M. Eng.) - Asian Institute of Technology
Keywords: Soil consolidation test; Soil mechanics